Sources of sub-micrometre particles near a major international airport - M. Masiol; M. Masiol; R. M. Harrison; R. M. Harrison; T. V. Vu; D. C. S. Beddows (Atmospheric Chemistry and Physics, 2017)
The international airport of Heathrow is a major source of nitrogen oxides, but its contribution to the levels of sub-micrometre particles is unknown and is the objective of this study. Two sampling campaigns were carried out during warm and cold seasons at a site close to the airfield (1.2 km). Size spectra were largely dominated by ultrafine particles: nucleation particles ( < 30 nm) were found to be  ∼ 10 times higher than those commonly measured in urban background environments of London. Five clusters and six factors were identified by applying k means cluster analysis and positive matrix factorisation (PMF), respectively, to particle number size distributions; their interpretation was based on their modal structures, wind directionality, diurnal patterns, road and airport traffic volumes, and on the relationship with weather and other air pollutants. Airport emissions, fresh and aged road traffic, urban accumulation mode, and two secondary sources were then identified and apportioned. The fingerprint of Heathrow has a characteristic modal structure peaking at  < 20 nm and accounts for 30–35 % of total particles in both the seasons. Other main contributors are fresh (24–36 %) and aged (16–21 %) road traffic emissions and urban accumulation from London (around 10 %). Secondary sources accounted for less than 6 % in number concentrations but for more than 50 % in volume concentration. The analysis of a strong regional nucleation event showed that both the cluster categorisation and PMF contributions were affected during the first 6 h of the event. In 2016, the UK government provisionally approved the construction of a third runway; therefore the direct and indirect impact of Heathrow on local air quality is expected to increase unless mitigation strategies are applied successfully.